On the Absence of Certain Island Effects in Mende - Smith, Jason D. (Languages (Basel), 2024)
The distinction between weak and strong islands has been extensively explored in the literature from both a descriptive and analytical perspective. In this paper, I document and analyze island constructions and constraints in Mende, an understudied Mande language spoken in Sierra Leone. Mende has both weak islands (left branch and wh-islands) and strong islands (adjunct clauses, sentential subjects, and coordinate structures). Intriguingly, it has a third class of islands, that I call mixed islands which show a subject–non-subject asymmetry in allowing for movement out of relative clauses, only when they modify the subject. As such, subject-modifying RCs cannot be classified as (strong/weak) islands in Mende. This is the first systematic work on islands and island constraints in the Mande language family, and, as such, it brings novel data from an understudied language family to bear on our understanding of A-bar dependencies and the study of island escape in African languages. It also calls into question a neat paradigm of cross-linguistic island constraints. Importantly, this work also lays down a baseline for future research on island constraints in the broader Mande language family. In order to discuss island constraints, this paper also lays out the first analysis of relative clauses in Mende, while integrating new research on the left periphery, focus constructions, and wh-constructions.